Global Virtual Teams Performance During the Digital Transformation - Liška, Radek (2022)
The dissertation is focused on the performance aspects of Global Virtual Teams (GVTs) from the perspective of digital transformation and forced virtuality. Firstly, a literature review focused on GVT discourse is introduced, followed by a description of the thesis methodology. The dissertation employs quantitative research based on computer-extracted data from a real-life working environment. Subsequently, a mixed effects modelling is carried out to evaluate the performance of GVTs using three key performance indicators (resolution duration, communication ambiguity, and quality reworks) and inspects the impact of forced virtuality on variables across diverse virtuality levels. Findings include specific sections for both the general and forced virtuality. Finally, the overall synthesis of the analysis provides a conclusion of the dissertation by merging analysis results with findings from a literature review and by listing implications for academic and practical utilisation of the presented findings and conclusions. Additionally, areas for further research are itemised alongside a list of referenced materials in this dissertation and appendixes